New Kazakh Alphabet: Sociolinguistic Problems and Their Solutions - Abasilov, А.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
Reflecting on the language policy, its subject and goals the author of the article gives answers to such questions as: what is caused by the need to make changes in the language, in its system and structure, how can a person influence the development of the language, as far as possible, and who plans and implements language policy? Different state and non-state agencies and institutions that deal with the problems of creating a normative-stylistic system of language, the formation and development of its terminology, the development of the alphabet and spelling are the main subject of planning language policy in many countries. It should be noted that the alphabet is one of the most important conscious actions for the formation of written speech and an important principle of linguistic policy. The author of the article notes that in any country and in any society the creation of the alphabet or its replacement is a nationwide and, above all, national problem, the solution of which should be approached in terms of political, cultural, linguistic, social and sociоlinguistic aspects and he valid the reasons. At the same time, he analyzes and shares his thoughts about the necessity to switch to the Latin alphabet, reasons for choosing a new alphabet and gives an analysis of the proposed projects on the transition to the Latin graphics.